PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS KOMPETENSI MASYARAKAT INDONESIA MASA ISLAM MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER(NHT) BAGI SISWA KELAS VII B SMP AL-ISLAM I SURAKARTA SEMESTER I TAHUN PELAJARAN 2013/2014 - Sutarmi, S. (HISTORIKA, 2017)
This study was conducted using classroom action research in two cycles. The subject of research was the 7th B graders of SMP Al-Islam 1 Surakarta. The objects of research were learning activity and outcome of Social Science.The result of research showed that Social Science learning using Numbered Head Together (NHT) conducted in two cycles could (1) improve the learning activity of students. Increasing of the studying activity look from the increasing activity from the early condition to the cycle II. a). Activity to express idea, ask and answer the questions in the early condition there are 12 students, there are 17 students in the cycle I, and there are 20 students in the cycle II. b). Cooperative activity in the discussion group, in the early conditionn there are 13 students, there are 16 studends in the cycle I, and there are 20 in the cycle II. c). Activity of reading lesson material, in the early condition there are 15, there are 18 in the cycle I, and there are 20 in the cycle. d). Activity of nothing, listening to the teacher’s explanation in the early condition there 15, and there are 19 in the cycle I, and there are 21 in the cycle II. e). Activity of presenting the group’s discussion result, in the early condition there 14, there are 18 in the cycle I , and there are 20 in the cycle II, (2) improve the learning outcome of students, as indicated with 28% (7 student) of score achieving KKM (Minimum Passing Criterion) increasing to 76% (19 student) in cycle I and to 88% (22 student)) in cycle II.